History of a strategy to eradicate poliomyelitis in Uruguay and Argentina - Alvarez, Adriana Carlina (2015)
The outbreak of poliomyelitis in the early 1950s turned it into one of the most feared diseases in the twentieth century. The resulting deaths and the thousands of children and adults who were handicapped world-wide made it a real threat which was only controlled with the introduction of the vaccines developed by Jonas Salk and Albert Sabin. This paper addresses the different health policies applied on both banks of the River Plate, starting in the 1950s. Soon after that, several Latin American countries, among which were Argentina and Uruguay, started oral vaccination programs. This paper attempts to answer questions related to the characteristics of the vaccination programs in each of the two countries and their relation to the degree in which the disease affected each of them. It is part of a more extensive research project dealing with the social, political and cultural consequences of the polio epidemics in twentieth-century Argentina with a view to understanding what happened in order to explain the present Post-Polio Syndrome (PPS)...